2019
DOI: 10.1016/j.jval.2018.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Financing of Drugs in the Netherlands: Past, Present, and Future—Results From Stakeholder Interviews

Abstract: Background: Conditional financing (CF) of hospital drugs was implemented in the Netherlands as a form of managed entry agreements between 2006 and 2012. CF was a 4-year process comprising 3 stages: initial health technology assessment of the drug (T ¼ 0), conduct of outcomes research studies, and reassessment of the drug (T ¼ 4). Objectives: To analyze stakeholder experiences in implementing CF in practice. Methods: Public and private stakeholders were approached for participation in stakeholder interviews thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Conditional reimbursement, or coverage with evidence development is the reimbursement of (new) healthcare interventions under a specific condition, often the requirement of collecting real-world (cost-)effectiveness data. It has been proposed as a policy-tool to delay the final reimbursement decision, decreasing the uncertainty on the (cost-)effectiveness and/or budget-impact of new interventions, while making these interventions available to patients at an early stage [42,43]. However, conditional reimbursement has also been described as creating a wedge effect, i.e.…”
Section: Implications For Conditional Reimbursementmentioning
confidence: 99%
“…Conditional reimbursement, or coverage with evidence development is the reimbursement of (new) healthcare interventions under a specific condition, often the requirement of collecting real-world (cost-)effectiveness data. It has been proposed as a policy-tool to delay the final reimbursement decision, decreasing the uncertainty on the (cost-)effectiveness and/or budget-impact of new interventions, while making these interventions available to patients at an early stage [42,43]. However, conditional reimbursement has also been described as creating a wedge effect, i.e.…”
Section: Implications For Conditional Reimbursementmentioning
confidence: 99%
“…The process to enter into performance-based MEAs, collect and analyse data, make decisions based on data analysed and to exit from MEAs should be transparent to ensure that stakeholders are accountable. In addition, governance processes should address independence, data ownership, audit, transparency, and appeal (Klemp, Frønsdal and Facey, 2011[4]; MacLeod and Mitton, 2010 [58]). It has been suggested that these should ensure "independence of the scheme from any parties with a vested interest in its outcomes", in particular independence of investigators and decision makers from influence by clinicians, patients and firms but also independence of investigators from payers (MacLeod and Mitton, 2010, p. 106 [58]).…”
mentioning
confidence: 99%
“…In addition, governance processes should address independence, data ownership, audit, transparency, and appeal (Klemp, Frønsdal and Facey, 2011[4]; MacLeod and Mitton, 2010 [58]). It has been suggested that these should ensure "independence of the scheme from any parties with a vested interest in its outcomes", in particular independence of investigators and decision makers from influence by clinicians, patients and firms but also independence of investigators from payers (MacLeod and Mitton, 2010, p. 106 [58]). While it may not be possible to achieve independence of investigators in practice because both payers and firms usually have an interest in the outcomes of MEAs and may also be involved in data collection and analysis, processes should minimise conflicts of interest and allow for independent scrutiny.…”
mentioning
confidence: 99%
“…However, reimbursement is unlikely for products manufactured under HE with an uncertain benefit/risk balance. Stakeholders are exploring financial models for hospital products, such as conditional financing [36].…”
Section: Discussionmentioning
confidence: 99%